Factors affecting the internet financial reporting (IFR) in banking sector companies listed on the indonesia stock exchange (IDX) - Ilham Ridho Maulana; Luciana Spica Almilia (Universitas Hayam Wuruk Perbanas, 2018)
Internet Financial Reporting is the disclosure of company’s financial and non-financial information through the company's official website. The format commonly used includes HTML, PDF, XBRL, audio and video. This study aims to examine the effect of firm size, leverage, listing age, profitability, and liquidity on the Internet Financial Reporting. The population in this study is banking sector companies listed on the Indonesia Stock Exchange (IDX) period 2016. The sampling technique used is purposive sampling with SPSS 23, software. The results of this study show that firm size and leverage have an effect on Internet Financial Reporting, but listing age, profitability, and liquidity have no effect on Internet Financial Reporting.